2018
DOI: 10.7196/sajbl.2018.v11i2.00643
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp in a clinical setting: The good, the bad and the law

Abstract: Giordano et al. [1] in 2017 published a systematic review article on WhatsApp Messenger (WhatsApp) as an adjunctive tool for telemedicine. Telemedicine is defined as the use of electronic communication technologies to provide healthcare support and information between a client and professional with expertise in the relevant field when separated by distance. They found a small number of eligible studies, which did not address ethics or security issues. It was concluded from their review that WhatsApp is a relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…This further highlighted the importance of quantifying the capsule oil content rather than relying on the declared value when determining the "true" EPA þ DHA content of encapsulated products. Many studies have reported lower than claimed EPA þ DHA levels in marine products available from Europe, [8,11] Australasia, [9,16,17,19,21,24] North and South America, [8,10,15,20,22,23] Korea, [12] and Africa, [13,14] and the current study is no exception. However, there is general disagreement between studies over what tolerance level is considered as being reasonably accurate to the label claim.…”
Section: Epa and Dha Contentmentioning
confidence: 46%
See 3 more Smart Citations
“…This further highlighted the importance of quantifying the capsule oil content rather than relying on the declared value when determining the "true" EPA þ DHA content of encapsulated products. Many studies have reported lower than claimed EPA þ DHA levels in marine products available from Europe, [8,11] Australasia, [9,16,17,19,21,24] North and South America, [8,10,15,20,22,23] Korea, [12] and Africa, [13,14] and the current study is no exception. However, there is general disagreement between studies over what tolerance level is considered as being reasonably accurate to the label claim.…”
Section: Epa and Dha Contentmentioning
confidence: 46%
“…In addition to the lower than claimed EPA þ DHA levels, several studies have also suggested that the oxidized content of marine oil supplements to be at a level that may be of concern with regards to quality. [9][10][11][12][13][14][15][30][31][32] In the present study, all sample products were found to have PV, p-AV, and TOTOX values below the respective limits of 10 meq kg À1 , 30, and 50, respectively, set out by the British and European pharmacopeial standards for fish oils [25] (Table 4), although TOTOX is not technically recognized by pharmacopeias as it is only considered a convenient measure of oxidation. [39] Nevertheless, 4 out of the 23 products analyzed (17.3%) had a PV greater than the 5 meq kg À1 limit recommended by the more stringent GOED Voluntary Monograph for EPA and DHA oils.…”
Section: Oxidative Status Of Encapsulated Oilsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,8] In spite of its widespread use, understanding and acknowledgement of the legal framework underpinning the group-sharing of confidential patient information are sorely lacking among HCPs. [7,9] Indeed, it is possible to forget that WhatsApp is a form of social media and to let one's guard down, e.g. by starting a personal interaction in a group setting that all group members can view.…”
Section: In Practicementioning
confidence: 99%